The Role of Productive Zakat In Promoting Economic Independence A Case Study of LAZISMU Pamekasan - Sri Wahyuni; Siti Maisaroh; Jaysal Vicry (DPPM Universitas Pelita Bangsa, 2025)
Poverty remains a significant issue in Indonesia, particularly in Pamekasan. This study examines the role of productive zakat managed by LAZISMU Pamekasan in fostering economic independence among mustahik (zakat recipients). Unlike consumptive zakat, productive zakat provides capital and skill training, enabling recipients to develop sustainable livelihoods. A qualitative approach, including in-depth interviews and participatory observation with mustahik and zakat managers, was employed. The findings reveal that productive zakat effectively increases mustahik’s income, facilitates the establishment of new businesses, and creates job opportunities. Furthermore, the program empowers mustahik to manage their businesses independently, significantly reducing dependence on consumptive zakat. The results highlight the potential of productive zakat in promoting economic independence and alleviating poverty sustainably. This initiative can serve as a replicable model for zakat institutions aiming to enhance community welfare through sustainable economic development